2021
DOI: 10.3389/fpls.2021.765089
|View full text |Cite
|
Sign up to set email alerts
|

Portable Measurement System for in situ Estimation of Oxygen and Carbon Fluxes of Submerged Plants

Abstract: The metabolism of submerged plants is commonly characterized by oxygen development. The turnover rates of carbon dioxide and other inorganic carbon species, however, are assessed only at distinct points in time after incubation or calculated through shifts in pH and total alkalinity. A novel three parameter measurement system was developed in order to improve this issue and to gain a better understanding of the metabolism of aquatic plants. It allows the simultaneous and continuous assessment of oxygen concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Therefore, it is necessary to improve the membrane in order to reduce the diffusion time and gas leakage. In the recent two decades, many novel sensors for the carbon dioxide measurements have been reported [149][150][151]. For example, Lu et al reported an in situ chemical pCO 2 sensor based on optical fiber for surface seawater (Figure 5b) [143].…”
Section: Sensors For Carbon Dioxide (Co 2 )mentioning
confidence: 99%
“…Therefore, it is necessary to improve the membrane in order to reduce the diffusion time and gas leakage. In the recent two decades, many novel sensors for the carbon dioxide measurements have been reported [149][150][151]. For example, Lu et al reported an in situ chemical pCO 2 sensor based on optical fiber for surface seawater (Figure 5b) [143].…”
Section: Sensors For Carbon Dioxide (Co 2 )mentioning
confidence: 99%